COVID-19 and trade facilitation in Southern Africa: Implications for the AfCFTA - Kudzai Mataba; Faizel Ismail (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
COVID-19 has created a trade crisis in Southern Africa, with a dramatic slowdown in cross-border trade. The crisis, which exposed weaknesses and deficiencies in the trade facilitation regimes, presents an opportunity for the African Continental Free Trade Area (AfCFTA) to address and contribute to greater levels of trade within Africa. This working paper looks at the impact of the border closures in response to the pandemic, and its impact on trade and the movement of goods in and out of the Southern African Development Community (SADC). The border closures in relation to trade facilitation in Southern Africa and the position of the SADC cluster of ministers of trade and transport are also considered. The paper argues that the AfCFTA should take the lead in addressing the long-term problems of weak trade facilitation systems and bring in measures that would advance greater intra-regional cooperation, including institutional responses and hard infrastructure. The paper concludes with policy recommendations.
Keywords: F15; R1; 330; COVID-19; cross-border trade; trade facilitation; regional integration; infrastructure